Pengaruh Keterampilan Mengajar dan Kedisiplinan Guru dalam Proses Belajar Mengajar - M. Saipul Watoni; Lalu A. Hery Qusyairi (AS-SABIQUN, 2021)
This research is entitled "The Influence of Teaching Skills and Teacher Discipline in the Teaching and Learning Process on Student Achievement in Social Studies Subjects for the 2020/2021 Academic Year". The aim of this research is to find out how much influence teaching skills and teacher discipline in the teaching and learning process (PBM) have on student achievement in social studies subjects. The approach used in this research is a quantitative approach with the type of survey research. The population used as subjects in this study were all Social Studies students of class VIII consisting of three classes at MTs NW Selebung for the academic year 2020/2021. In this study, the technique used in sampling is a random sampling technique with the class as the sample unit so that all students are studied randomly by providing equal opportunities to all members of the population, the minimum sample size is 50.98 so 51 students will be taken from class VIII MTs NW Selebung. The main data collection technique in this research is to use a closed questionnaire given to all students who are the research sample, there are two types of questionnaires used in collecting data in this study, namely a questionnaire about teaching skills and teacher discipline which will be filled out by students. For data analysis techniques used Pearson product moment analysis techniques, t-test (t-test) and multiple correlation. Based on the results of the calculations obtained coefficient t count of 5.75 with a contribution of 31.58% for teacher teaching skills, t count of 4 .42 with a contribution of 23.43% for teacher discipline, t count of 9.33 with a contribution of 27.98% for teaching skills and teacher discipline, with a significance level of 5%, dk = 51 obtained t table of 4.08 means that t count t table, thus there is a significant influence on teacher teaching skills, teacher discipline as well as teaching skills and teacher discipline together in the teaching and learning process in social studies subjects at MTs NW Selebung for the academic year 2020/2021.